Oxymatrine-based bioacaricide as a management tool against Oligonychus ilicis (McGregor) (Acari: Tetranychidae) in coffee - Júnior de Andrade, Daniel [UNESP] (2020)
The acaricidal bioactivity of an oxymatrine-based commercial formulation was assessed against Oligonychus ilicis (McGregor) (Acari: Tetranychidae), a pest in coffee cropping systems. For this purpose, a series of assays were carried out under laboratory and greenhouse conditions using different concentrations (from 0.25 to 1.0 mL c.p. L−1) of the oxymatrine formulation. In the laboratory, a significant reduction in egg hatchability was observed in treatment using 1.00 mL c. p. L−1 of the oxymatrine formulation. Egg hatchability rates ranging from 69.9 to 91.7% were observed in eggs treated with 0.25–0.75 mL c. p. L−1 of the bioacaricide. Although the ovicidal activity was low, all tested bioacaricide concentrations caused significant larval mortality for newly hatched larvae in relation to the negative control. For adult females, the highest concentrations (0.75–1.00 mL c. p. L−1) of the bioacaricide caused high acute toxicity and residual (≥86.7% mortality) at 10 days after exposure, which were similar to the synthetic acaricide spirodiclofen. In the greenhouse, the bioacaricide caused ~74% reduction in population levels of O. ilicis, while spirodiclofen provided a population reduction of ~96%. In this study, no phytotoxic effect was observed on the coffee nursery trees treated with the bioacaricide. The oxymatrine-based commercial formulation has potential to be used for O. ilicis management in coffee, though field trials are needed to validate findings of our study.